GEOPOLITICAL (NON) OPPORTUNITIES VS. "LATE" RESPONSE OF THE FOREIGN POLITICAL SERVICE OF NORTH MACEDONIA IN THE PROCESS OF EUROPEAN INTEGRATION - Jelisavac Trošić, Sanja; Mitko, (Serbian political thought, 2024)
In the case study of the foreign policy of North Macedonia, we can clearly see how global events, viewed from the perspective of geopolitical circumstances, do not always and as a rule have a direct impact on national internal and regional events in the Western Balkans, nor on the foreign policy actions of the Western Balkan six. In the paper, four determinants were singled out, on the basis of which explanations were provided, in a scientific and research context, why the foreign policy mechanism of North Macedonia "failed" in the process of achieving defined foreign policy goals, above all the basic goal - the country's accession to the European Union. At the same time, the lack of effectiveness of foreign policy action was not in a cause-and-effect relationship with wider European and international geopolitical circumstances. The internal armed conflict in North Macedonia, which threatened to develop into a civil war between the dominant ethnic communities of Macedonians and Albanians, is the first indicator, i.e. the determinant of the explanation why the foreign policy mechanism of North Macedonia “failed” in the process of this country joining the European Union.Another significant moment that was missed in the European integration process of Skopje, covers the period from 2006 to 2017 with two stages: the period leading up to the NATO Summit in Bucharest in 2008 and the period after this summit, up to the change of power of former Prime Minister Nikola Gruevski, which has led to a multiple crisis within that country. The postponement of North Macedonia's accession to NATO in 2008, due to Greece's express refusal, with a focus on connecting the Macedonian nation with the heritage of the ancient Macedonians, with the simultaneous suspension of democratic capacities and principles that represent significant determinants in the process of joining the European Union, leads to missing out and moving away from the path accelerated European integration of North Macedonia.As a third determinant, pervasive corruption was singled out, which affected all levels of government, so that the internal circumstances in North Macedonia actually “worked to the advantage” of the European Union, which at that time as a whole, and also individual member states of the Union, were also moving further away from the policy of enlargement as a mechanism in the process of European integration of both North Macedonia and the remaining countries of the Western Balkans.The aforementioned challenges, which North Macedonia has been facing for almost thirty years, are not in a cause-and-effect relationship with external, whether regional, European or international, geopolitical circumstances and trends. We are talking about challenges that, regardless of the geopolitical dimension of the enlargement of the European Union from the point of view of Brussels and the member states of the European Union, significantly affect the dynamics of North Macedonia's accession to the European Union, that is, the effectiveness of the process of realizing this strategic foreign policy goal.However, it is important to mention the foreign policy action of North Macedonia from the point of view of international law and the provisions of the UN Charter, which represents a strong fourth determinant in the context of the realization of North Macedonia's foreign policy goals. Here, it was possible to see how the international positioning of North Macedonia is conditioned to the detriment of the provisions and norms of international law. In this way, the principles of equality, sovereignty and political independence were placed in a subordinate position in relation to the factual political powers in interstate relations, directly harming the principle of self-determination, in the context of the identity attributes of North Macedonia and the Macedonian people.In the period when geopolitical circumstances were favourable to North Macedonia, the opportunity for this country to become a member of the European Union was missed, thus achieving a strategic foreign policy goal, which in the context of the EU did not cause any consequences when it comes to the EU itself. However, the consequences for North Macedonia itself remained and only in the following period did the circumstances worsen and lead this country to a longer and more difficult path to accession. The future policy should be based on strong tactical tools, which are sufficiently flexible in relation to regional and international trends. First of all, North Macedonia needs a strong internal institutional infrastructure, which simultaneously ensures political, social and economic stability and predictability. In this way, it would be possible to realize the established goals of the foreign policy of North Macedonia.
Keywords: small and micro states; foreign policy goals; geopolitical circumstances; internal challenges; European Union; North Macedonia